Geothermal energy utilization in the Bükkalja region by reusing abandoned hydrocarbon wells - Bretán, Dávid; Szűcs, Péter; Miklós, Rita; Ilyés, Csaba (International Journal of Engineering and Management Sciences, 2019)
Hungary is a country in an inactive volcanic area, but with a geothermal potentical recognized bot hat European and international level. The geothermal gradient of the country is ~ 45°C/km on avarage, while in other countries it is ~ 20-30 °C/km. Accordingly, the temperature can reach 55-60°C at 1 km and 100-130°C at depths of 2 km. There are many types of extraction and utilization of geothermal energy, of which a large group is energy recovery . This direction is not typical in Hungary, so it is worth developing. The developement of the sector is slow due to high initial invertment demand and the long planning phase. On the one hand, the aim of our reserach is to take steps to remedy this problem by examining the funcion change of a barren well. Int he foreground and peripheral areas of the Bükk Mountains, there are numerous unused hydrocarbon wells, which our work is examining for energy purposes with a view to their later utilization. The present study focuses on 13 abandoned wells in the Pünkösd Mountain, area of Bükkalja, Demjén.